f(x) = x^2 + 5x - 6
what two number multiply together to give us -6 and add to give us 5
-1 *6 = -6
-1 +6 =5
(x-1) (x+6) = 0
using the zero product property
x-1 =0 x+6 = 0
answer: i’m a hundred percent correct it’s 5/4.
step-by-step explanation: this is because you move the constant which is p to the right and add the fractions 1/2 and 3/4.
x = 2 is the vertical asymptote
y = 5 is the horizontal asymptote
the vertical asymptote is when it is undefined, or when the denominator is 0. this is when x = 2.
to find the horizontal asymptote, we need to find the value y can never be. notice 1/(x-2) is never 0, so when y = 5, that value has to be 0, but this is not possible, so y = 5 is the vertical asymptote.
what is the value of t?